Financial Contagion and Investor "Learning" : An Empirical Investigation - Basu, Ritu (IMF Working Papers; Working Paper ;, 2002)
There have been several episodes of financial market "contagion" in the 1990s. Is contagion driven by herd behavior? Does it reflect fundamental economic linkages between countries? Or are episodes of contagion driven by investor learning and risk reassessment about a select group of countries? We pursue these questions by studying the persistence in the spillover of shocks following the bond market developments in Hong Kong SAR in 1997. Our results suggest that this contagion, at least for a few countries, was a consequence of adverse sentiment shifts arising from investor learning and was not merely driven by changes in fundamentals.